Pemaknaan terhadap Dendang Mengasuh Anak (Kajian Semantik) - Kasmi Waldisen Manrates; Lindawati Lindawati; Eka Meigalia (Universitas Andalas, 2018)
This paper aims to identify the type of semantic meaning and identify the meaning contained in the dendang lullabies.The methods and techniques used in this study consist of three stages: 1) methods and techniques for providing data, the referral method and the basic techniques which are tapping techniques and advanced techniques, Simak Libat Cakap (SLC) and recording; 2) data analyzed with translational methods: Pilah Unsur Penentu (PUP) technique. The results show cognitive meaning, connotative meaning, lexical meaning, and grammatical meaning in the object. The meaning contained implies useful in society, nationalism, life spirit, mastery of things, position in society, can eliminate the maternal disease, provident and pride.